Handbook of the biology of aging - Musi, Nicolas; Hornsby, Peter J. (Handbooks of aging., 2021)
"Handbook of the Biology of Aging, Ninth Edition, provides a comprehensive synthesis and review of the latest and most important advances and themes in modern biogerontology. The book focuses on the trend of "big data" approaches in the biological sciences, presenting new strategies to analyze, interpret and understand the enormous amounts of information being generated through DNA sequencing, transcriptomic, proteomic, and metabolomics methodologies applied to aging related problems. Sections cover longevity pathways and interventions that modulate aging, innovative tools that facilitate systems-level approaches to aging research, the mTOR pathway and its importance in age-related phenotypes, and much more."--Publisher's description.